2022
DOI: 10.1111/jce.15656
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal safety in CLOSE‐guided 50 W high‐power‐short‐duration pulmonary vein isolation: The PREHEAT‐PVI‐registry

Abstract: Introduction: Pulmonary vein isolation (PVI) using high-power-short-duration (HPSD) radiofrequency ablation (RF) is emerging as the standard of care for treatment of atrial fibrillation (AF). While procedural short-term to midterm efficacy and efficiency are very promising, this registry aims to investigate esopahgeal safety using an optimized ablation approach.Methods: In a single-center experience, 388 consecutive standardized first-time AF ablation were performed using a CLOSE-guided-fixed-50 W-circumferent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…In the POWER‐AF study, using 45 W in the posterior wall required an average of 13 s (range: 11–14 s) to achieve a target AI of 400 9 . Similar ablation duration was required to reach AI of 400 using 50 W in this study, with maximum RF duration on the posterior wall reported up to 19.9 ± 3.5 s in patients who developed EDEL 5 . As acknowledged by the authors in the Discussion, there is a more narrow safety margin with high power ablation, and therefore prolonged high power applications may negate the safety benefits of HPSD biophysics 3,9 .…”
supporting
confidence: 60%
See 3 more Smart Citations
“…In the POWER‐AF study, using 45 W in the posterior wall required an average of 13 s (range: 11–14 s) to achieve a target AI of 400 9 . Similar ablation duration was required to reach AI of 400 using 50 W in this study, with maximum RF duration on the posterior wall reported up to 19.9 ± 3.5 s in patients who developed EDEL 5 . As acknowledged by the authors in the Discussion, there is a more narrow safety margin with high power ablation, and therefore prolonged high power applications may negate the safety benefits of HPSD biophysics 3,9 .…”
supporting
confidence: 60%
“…9 Similar ablation duration was required to reach AI of 400 using 50 W in this study, with maximum RF duration on the posterior wall reported up to 19.9 ± 3.5 s in patients who developed EDEL. 5 As acknowledged by the authors in the Discussion, there is a more narrow safety margin with high power ablation, and therefore prolonged high power applications may negate the safety benefits of HPSD biophysics. 3,9 Steam pops have been shown to occur before target AI of >450 are reached when using high power ablation, particularly at higher starting impedances.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…showing significantly higher EDEL rates of nearly 12% with a CLOSE-guided 50 W protocol with target AI values of 550/400. 34 Notably, again posterior box lesion did not increase EDEL risk. Reduction of target AI for posterior lesions from 380 to 350/320 was associated with reduced occurrence of EDEL as well as gastroparesis.…”
Section: Discussionmentioning
confidence: 88%